Determination and Distribution of Phthalate Diesters in Plastic Bottled Beverages Collected in Hanoi, Vietnam - Manh Tri, Tran; Minh Thuy, Le; Thi Ngoc Anh, Nguyen; Thi Trinh, Le; Quang Huong, Le; Thi Phuong Thao, Pham; Quang Trung, Nguyen (VNU Journal of Science: Natural Sciences and Technology; Vol 34 No 4DO - 10.25073/2588-1140/vnunst.4822, 2018)
Abstract: Phthalates, industrial synthetic chemicals, are widely used to improve the flexibility of plastics. The more plastic products are used, the more phthalates are found in the environment. In spite of their significant benefits to our lives and industry, their bad effects on laboratory animals have been recorded in some studies. Nevertheless, until now the understanding of the occurrence, distribution, and risk of human exposure to phthalates has been limited in Vietnam. This study introduces a gas chromatography system in combination with mass spectrometry for analyzing nine phthalates in the beverage samples collected in Hanoi (Vietnam). The linearity ranged from 1.00 to 1,000 ng/mL with R 2 ≥ 0.998. The method detection limits (MDLs) and method quantitative limits (MQLs) of phthalates in the beverage ranged from 0.01 to 0.05 ng/mL and 0.03 to 0.15 ng/mL, respectively. The recoveries of surrogate compounds ranged from 73.4 ± 5.5% ( d 4 -DPP) to 91.6 ± 9.9% ( d 4 -BzBP), with RSD≤10.7%. The total concentrations of phthalates in several brands of beverage collected in Hanoi were found ranging from 18.2 to 86.0 ng/mL. Among the studied phthalates, the concentrations of di(2-ethylhexyl)phthalate (DEHP) and di( n -octyl)phthalate (DnOP) were found much higher than the others’. However, the concentrations of phthalate in all the studied samples were below the maximum residual level specified in the relevant Vietnamese regulations. Keywords: Phthalates, DEHP, beverage, plastic bottle, GC/MS. References [1] Diane, K., Rong, W., Ricchard, P. M., Jiping Z., 2011. Phthalates in cosmetic and personal care products: Concentrations and possible dermal exposure. Environ. Res. 111: 329-336. [2] Heudorf, U., Merscha-Sundermann V., Angerer J.,2007. Phthalates: Toxicology and exposure. Int. J. Hyg. Environ. Health 210(5): 623-634. [3] Koch, M.H., Calafat, M.A.,2009. Human body burdens of chemicals used in plastic manufacture. Philos. Trans. R. Soc. B Biol. Sci. 364: 2063-2078 [4] Guo, Y., Wang, L., Kannan, K.,2014. Phthalates and parabens in personal care products from China: concentrations and human exposure. Arch. Environ. Contam.Toxicol.66(1): 113-119. [5] Hubinger, J.C., Havery, D.C.,2006. Analysis of consumer cosmetic products for phthalate esters. J. Cosmet. Sci. 57(2): 127-137. [6] U.S. EPA (U.S. Environmental Protection Agency), 2008. Child-Specific Exposure Factors Handbook (final report) Available at: https://cfpub.epa.gov/ncea/risk/recordisplay.cfm?deid=199243 Accessed 10 Feb 2017. [7] Kamrin, M.A.,2009. Phthalate Risks, Phthalate Regulation, and Public Health: A Review. J. Toxicol. Environ. Health, Part B, Critical Reviews, 12(2): 157-174. [8] Martino-Andrade, A.J., Chahoud, I.,2009. Reproductive toxicity of phthalate esters. Mol. Nutr. Food Res. 54: 148-157. [9] Guo, Y., Kannan, K.,2012. Challenges encountered in the analysis of phthalate esters in foodstuffs and other biological matrices. Anal. Bioanal. Chem. 404(9): 2539-2554. [10] Guo, Y., Zhang, Z., Liu, L., Li, Y., Ren, N., Kannan, K.,2012. Occurrence and Profiles of Phthalates in Foodstuffs from China and Their Implications for Human Exposure. J. Agri. Food Chem. 60(27): 6913-6919. [11] Tran, M.T., Kannan, K., 2015. Occurrence of phthalate diesters in particulate and vapor phases in indoor air and implications for human exposure in Albany, New York, USA. Arch. Environ. Contam.Toxicol. 68: 489-499. [12] Guo, Y., Alomirah, H., Cho, S.H., Minh, B.T., Mohd, A.M., Nakata, H., Kannan, K. (2011) Occurrence of Phthalate Metabolites in Human Urine from Several Asian Countries. Environ. Sci. Technol. 45(7): 3138-3144. [13] Carly, H., 2009. New Law banning phthalates from Children’s toys takes effects,mother Earth living, Feb 2009, http://www.motherearthliving.com/green-living/new-law-banning-phthalates.aspx. [14] The maximum residual level of DEHP in food. Ministry of Health. 2011. Number 2204/QD-BYT. [15] Iman, A.S., Neptune, S. Ammar, A.,2011. Phthalates residues in plastic bottled waters. J. Toxicol. Sci. 36(4):469-478. [16] Bosnir, J., Puntaric, D., Galic, A., Skes, I., Dijanic, T., Grgic, M., Curkovic, M., Smit, Z. 2007. Migration of phthalates from plastic containers into soft drinks and mineral water. Food Technol. Biotechnol., 45:91-95. [17] Schecter, A., Lorber, M., Guo, Y., Wu, Q., Yun, H.S., Kannan, K., Homel, M., Imran, N., Linda S.H., Dunlei, C., Justin, A.C., Linda, S.B., 2013. Phthalate concentrations and dietary exposure from food purchased in New York, State. Environ. Health Pers. 121(4): 473-494. [18] Tine, F., Kelly, S., Mijra, V.H., Lieve, G., Stefaan, D.H., Isabelle, H., Guido, V., Analysis of phthalates in food products and packaging materials sold on the Belgian market. Food Chem. Toxicol. 50(7): 2575-2588. [19] Mohammed, F., Zaater, Y.R., Tahboub, A.N., Al, S.,2014. Dermination of Phthalates in Jordanian Bottled Water using GC-MS and HPLC-UV: Environmental Study. Journal of Chromatographic Science, 52(5): 447-452. [20] Ping-Gu, W., Xiao-Dong, P., Bing-Jie, M., Li-Yuan, W., Jin, Z., 2014. Dermination of phthalate esters in non- alcoholic beverages by GC-MS and optimization of the extraction conditions. European Food Research and Technology. 238(4): 607-612.